The anatomic characteristic of aSedum acre L, caustic from various ecological conditions of South and the Central Kazakhstan - Akhmetzhanova, A.I.; Аuyelbekova A.K.; Kyzdarova, D.K. (Fundamental and Experimental Biology, 2016)
The purpose of the this work was comparative studying of a morphological-anatomical structure of vegetative organs of Sedum acre L. from various conditions of growing. When comparing the cuts received from various ecological growth conditions it is visible that in the conditions of the Central Kazakhstan the leaf of a Sedum acre L. in a cross cut differs in the smaller size of cells, powerful development of a cuticle. It isn’t revealed special distinctive signs in the conductive system. It isresult of that soil climatic conditions of Southern Kazakhstan that are optimum for growth and cultivation of a Sedum acre L. Thus, as a result of carrying out the morphological-anatomical analysis of vegetative organs of Sedum acre L. from various growth conditions it is established that with the general signs in their structure along there is more and less expressed distinctions which are explained by differences of growth place climatic factors.